Structure and mechanical properties of polyamide 6/Brazilian clay nanocomposites - Amanda Melissa Damião Leite; Edcleide Maria Araujo; Rene Anisio da Paz; Osanildo Damião Pereira; Hélio Lucena Lira; Edson Noriyuki Ito (Materials Research, 2009)
Recent interest in polymer/organoclays nanocomposites systems is motivated by the possibility of achieving enhanced properties and added functionality at lower clay loading as compared to conventional micron size fillers. By adding montmorillonite clay to polyamide 6 increases the Young modulus, yield strength and also improves barrier properties. In this work, nanocomposites of polyamide 6 with montmorillonite clay were obtained. The clay was chemically modified with three different quaternary ammonium salts such as: Dodigen, Genamin and Cetremide. In this case, a dispersion of Na-MMT was stirred and a salt equivalent to 1:1 of cation exchange capacity (CEC) of Na-MMT was added to the dispersion. The montmorillonite clay (untreated and treated by ammonium salts) and nanocomposites were characterized by X ray diffractions. Also the nanocomposites were characterized by transmission electron microscopy and mechanical properties. The results indicated that all the quaternary ammonium salts were intercalated between the layers of clay, leading to an expansion of the interlayer spacing. The obtained nanocomposites showed better mechanical properties when compared to polyamide 6. The clay acted as reinforcing filler, increasing the rigidity of nanocomposites and decreasing its ductility.